Pengaruh Program Csr Internal Dan Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan Pada Pt Alex Putra Group Dikota Cilegon - Falaah, Miftahul; Murad, Anizir Ali; Sunaryo, Deni (Universitas Serang Raya, 2018)
The purpose of this risetto determine the effect on each dependent variable Effect of CSR Internal(X₁) and Physical Work Environment (X₂) on the dependent variable Employee Job Satisfaction (Y). In this study data was collected through a questionnaire method for 39 respondents who worked at PT. Alex Putra Group Cilegon. The analysis used was multiple linear analysis using data analysis techniques that have fulfilled the validity, reliability test and classical assumption test, so as to produce the regression equation as follows:Y = 16,736 + 0,406 X₁ + 0,731 X₂ + e, The results of the analysis found that both the Internal Corporate Social Responsibility Program variables and the Physical Work Environment had a significant influence on Employee Job Satisfaction. The adjusted R Square figure of 0.150 shows that 15 percent variation in Employee Job Satisfaction can be explained by the two dependent variables used in the regression equation. While the remaining 85 percent is explained by other variables outside the two variables used in this study. Keywords: internal corporate social responsibility program, physical work environment, and employee job satisfaction